1996
DOI: 10.1128/jb.178.9.2521-2526.1996
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of guanine and hypoxanthine phosphoribosyltransferases in Methanococcus voltae

Abstract: Phosphoribosyltransferase (PRTase) and nucleoside phosphorylase (NPase) activities were detected by radiometric methods in extracts of Methanococcus voltae. Guanine PRTase activity was present at 2.7 nmol min ؊1 mg of protein ؊1 and had an apparent K m for guanine of 0.2 mM and a pH optimum of 9. The activity was inhibited 50% by 0.3 mM GMP. IMP and AMP were not inhibitory at concentrations up to 0.6 mM. Hypoxanthine inhibited by 50% at 0.16 mM, and adenine and xanthine were not inhibitory at concentrations up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
(44 reference statements)
0
15
0
Order By: Relevance
“…These results suggested the presence of nucleotide salvage pathways, which presumably could incorporate base analogs to form toxic nucleotides. The presence of guanine phosphoribosyltransferase and Hpt activities was confirmed in M. voltae, and spontaneous mutants resistant to base analogs lacked these activities (6).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…These results suggested the presence of nucleotide salvage pathways, which presumably could incorporate base analogs to form toxic nucleotides. The presence of guanine phosphoribosyltransferase and Hpt activities was confirmed in M. voltae, and spontaneous mutants resistant to base analogs lacked these activities (6).…”
mentioning
confidence: 85%
“…The previously observed sensitivity of M. maripaludis to 8-azahypoxanthine could be attributed to Hpt encoded by the hpt gene (6,7,14). We constructed a plasmid containing an in-frame deletion in the hpt gene, flanked by 0.9 kb of upstream DNA and 1.4 kb of downstream DNA.…”
Section: Maripaludis Can Use L-or D-alanine As a Nitrogen Sourcementioning
confidence: 99%
“…Taken together, these data suggest that HX-containing nucleosides and nucleotides potentially predated guanine-containing nucleotides and nucleosides. This is also supported by the annotated adenine phosphoribosyltransferase (encoded by MJ1655) and its homologues from M. thermautotrophicus and Methanocococcus voltae, which were all demonstrated to be specific for HX and guanine, showing no activity toward adenine (39,40;Miller,unpublished). The presence of these enzymes demonstrates that M. jannaschii, and possibly other methanogens, is unable to use adenine for the salvage of purines and require conversion to HX prior to salvage of the nitrogen-rich purine ring.…”
Section: Discussionmentioning
confidence: 71%
“…The possibility of developing such a system in archaea is supported by several studies of purine and pyrimidine salvage pathways (6,7,17,32,36). In addition to demonstrating the presence of base salvage pathways, it was observed that spontaneous resistance to purine analogs is associated with decreased activity of certain purine salvage enzymes.…”
mentioning
confidence: 66%
“…We suspect that de novo synthesis is repressed in this medium and that the adaptation period required for prototrophic growth involves switching from the salvage pathway back to the de novo pathway. In some methanoarchaea, purine salvage mutants have been isolated by selecting resistance to purine analogs (6,7,17,32,36). Therefore, we tested wild-type M. acetivorans and the hpt1::mini-mar strain for sensitivity to a number of purine analogs (Table 3).…”
Section: Resultsmentioning
confidence: 99%